Distribution of Onryza maga (Leech, 1890) (Lepidoptera: Hesperiidae) with description of female genitalia and taxonomic notes - Xue, Guoxi; Li, Yufei; Liu, Zihao; Ren, Yingdang (Entomologica Fennica, 2016)
For more than twenty years, Hainan, Vietnam, Myanmar, Thailand, Malaysia, Singapore and Indonesia have been erroneously reported in Chinese literature as belonging to the distribution range of Onryza maga (Leech 1890). Based upon a careful survey of specimens and relevant literature, these regions are omitted from the known range of this species. Onryza maga maga is found from northeast Guizhou, south Henan and Qinling-Daba Mountains in Shaanxi of China, its occurrence in Hunan is confirmed. The adults are redescribed and the variability of wing patterns is discussed. Female genitalia are illustrated and described for the first time. Some biological information and an updated distribution map of the species are provided.